2016
DOI: 10.1590/0100-67622016000100003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential of Seed Rain as an Alternative for Forest Restoration in Permanent Preservation Areas1

Abstract: -The ecological restoration of degraded areas using seeds collected in forest remnants has shown significant results. This study was developed to verify the potential of seed rain to regenerate forest fragments of a Permanent Preservation Area (PPA) in the Apa River Basin which is located in the southwestern portion of the Mato Grosso do Sul state, Brazil. To develop the study, we installed 25 collectors measuring 1 m 2 each, which were systematically distributed on an area of 1.5ha. Seed gathering was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…1). Some previous studies have set up a similar number of traps (12–33) or a similar area covered by traps (4.5 – 30 m 2 ) (César et al., 2017; da Silva et al., 2016; Labatore et al., 2017; Piña-Rodrigues & Aoki, 2014;); therefore, sampling efforts are comparable. All traps were placed in the areas of extensive management of the selected home gardens because they offer better conditions for plant establishment than intensively managed area does.…”
Section: Methodsmentioning
confidence: 99%
“…1). Some previous studies have set up a similar number of traps (12–33) or a similar area covered by traps (4.5 – 30 m 2 ) (César et al., 2017; da Silva et al., 2016; Labatore et al., 2017; Piña-Rodrigues & Aoki, 2014;); therefore, sampling efforts are comparable. All traps were placed in the areas of extensive management of the selected home gardens because they offer better conditions for plant establishment than intensively managed area does.…”
Section: Methodsmentioning
confidence: 99%
“…Among these species, Samanea tubulosa (Benth.) Barneby & JW Grimes has been used in the restoration and maintenance of ecosystems in degraded areas [6,7], being characterized as a typical tree in the Cerrado biome, reaching up to 28 m in height and 1 m in diameter, widely used in forestry, ornamentation and as part of animal nutrition [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The use of commercial substrates that are based on expanded vermiculite and organic materials [13] is costly [7,14], however, decomposed organic residues and fractions from Brazilian pre-Amazonian palms, such as babassu (Attalea speciosa Mart. ), buriti (Mauritia vinifera Mart.…”
Section: Introductionmentioning
confidence: 99%
“…Seed dispersal is critical for the recruitment of new individuals (Schupp & Fuentes, 1995; Nathan & Muller‐Landau, 2000) and a key process for the regeneration of plant populations and communities (Howe & Smallwood, 1982). Recruitment may occur immediately upon the arrival of seeds to the ground after seed dispersal from the mother plant (i.e., seed rain), or be delayed through the formation of transient or permanent soil seed banks (Uhl et al , 1981; Álvarez‐Buylla & Martínez‐Ramos, 1990; Moles & Drake, 1999; Vandvik et al , 2016; Silva et al , 2016). The relative importance of these two primary regeneration sources conforms to a remarkable evolutionary dilemma with variations among habitats (Thompson, 2000; Vandvik et al , 2016), and its clarification is a crucial step to understand the community structure and composition and to apply appropriate management measures.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to establish soil banks has been studied in relation to a few plant functional traits, e.g. regeneration guild (Vázquez‐Yanes & Orozco Segovia, 1984; Garwood, 1989; Chandrashekara & Ramakrishnan, 1993; Vázquez‐Yanes & Orozco Segovia, 1993; Rees, 1997), life form (Garwood, 1989; Rees, 1997; Silva et al , 2016), seed chemistry (Thompson, 2000), seed size and dispersal capacity (Bakker et al , 1996; Thompson, 2000; Valenta et al ., 2015; Douh et al , 2018; Ssali et al , 2018), and phenology (Salazar et al , 2011; Heydel & Tackenberg, 2017). For instance, observational studies suggested that large seed size and long dispersal distance should be negatively related to persistence in the soil (Klinkhamer et al , 1987; Bakker et al , 1996; Thompson, 2000).…”
Section: Introductionmentioning
confidence: 99%